(untitled) (Encuentros, 2023)
This research, more than an academic work that yielded quantitative or qualitative results, involves a deliberation on the scholar discourse in relation to the project of an ethical reflection under the parameters of ’good-living’. Under the above premise we adopt the ontosemiotics or semiotics of subjectivity-affectivity, whose main argumentative postulate lies in the consideration of the subject as a text that can be read through the enunciative quadrant: author-text-reader-context. In this sense, this researching is aimed at evidencing whether the scholar discursive action points to the recognition of the school subject as a transcedental subject; hat is, the recognition of a conscious and consistent subject within the framework of the pedagogical relationship, in the environment of the family and that is reflected, in general, collectively in the society in which its existence transits.